2022
DOI: 10.2147/jir.s350003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Cytokine Profiling: A Novel Method for Early Prediction of the Efficacy of Sublingual Immunotherapy in Allergic Rhinitis Patients

Abstract: Background Allergic rhinitis (AR) is a common inflammatory airway disease, and allergen-specific immunotherapy (AIT) is the only disease-modifying treatment for it. However, not all AR patients respond to AIT, and early prediction of patient response is extremely important. This study aimed to example serum levels of multiple cytokines in AR and explore their association with the efficacy of AIT. Methods A total of 74 AR patients treated with sublingual immunotherapy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…High serum periostin levels were observed after HDM-SLIT, indicating that serum periostin appears to be a useful biomarker in AIT ( 109 ). Furthermore, multiple cytokines profiling was investigated in treated AR patients with SLIT where serum BAFF, IFNγ, IL10, and IL33 levels were strongly predictive of the efficacy of SLIT ( 110 ). These sets of biomarkers are closely associated with Th1 immune response and type 2 innate lymphoid cells downstream signaling pathway in AR.…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%
“…High serum periostin levels were observed after HDM-SLIT, indicating that serum periostin appears to be a useful biomarker in AIT ( 109 ). Furthermore, multiple cytokines profiling was investigated in treated AR patients with SLIT where serum BAFF, IFNγ, IL10, and IL33 levels were strongly predictive of the efficacy of SLIT ( 110 ). These sets of biomarkers are closely associated with Th1 immune response and type 2 innate lymphoid cells downstream signaling pathway in AR.…”
Section: Treatment Of Allergic Rhinitismentioning
confidence: 99%
“…33 In a study with 1-year follow-up, baseline S100A11 concentrations were found to predict the effectiveness of sublingual AIT, with an AUC of 0.76, in patients with AR. 34 Furthermore, in a randomized, open-label controlled trial, Hoshino et al reported that serum periostin levels could distinguish sublingual AIT responders from nonresponders in adult AR patients allergic to HDM, with a cutoff value of 30.2 ng/mL and an AUC of 0.79. 35 However, it is important to note that these previous studies have primarily focused on individual immune markers.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, allergic inflammation is linked with a shift in the ratio of Th1 to Th2 cell production of cytokines towards a Th2 predominance [45]. Due to natural allergen exposure, Th2 lymphocytes proliferate with the release of cytokines such as IL-1, IL-3, IL-4, IL-5, IL-6, IL-9, IL-10, IL-13, IL-17A, IL-18 and GM-CSF, and these inflammatory mediators play important roles in the pathogenesis of AR [46][47][48]. In the present study, the flow cytometrybased immunofluorescent assay kit was used to detect the levels of human cytokines in nasal mucosa IL-1β, IFN-α2, IFN-γ, TNF-α, MCP-1 (CCL2), IL-6, IL-8 (CXCL8), IL-10, IL-12p70, IL-17A, IL-18, IL-23 and IL-33 in adolescents with AR with different severity of the disease.…”
Section: Discussionmentioning
confidence: 99%